Y'all eat yet? : welcome to the pretty b*tchin' kitchen - Lambert, Miranda, 1983-; Gleason, Holly (Dey Street Books, 2023)
If you're going to have a Bitchin Kitchen, you're going to need a few things--plenty of room, plenty of good food for sharing, high spirits (in both senses) and all the friends and family you can fit. For Miranda Lambert, a good time means sharing a great meal with the women who helped raise her back in Texas--her mom and a colorful bunch of best friends who could raise the roof, come through in a pinch, celebrate, cry, and really, really cook. Miranda Lambert invites readers into this special circle of sisterhood with collection of recipes and stories. Y'all Eat Yet? is full of recipes for meals that fill your belly, and your soul, food meant to be shared, meant to be eaten with your fingers off of paper plates, or on your fanciest antique China. Some were handed down to Miranda from her mom and grandma, some come from the circle of cherished friends who helped raise her, and all of them are meant to be easy to prepare and shared with those you love. True to Miranda's personality, Y'all Eat Yet? is sassy and inviting. Whether she's cooking up omelets in her tricked-out Airstream to serve with Mimosas or laying out the Whiskey cupcakes next to Nonny's Banana pudding, Y'all Eat Yet? delivers food you want to make alongside charming stories that show just why Miranda Lambert is one of the most beloved artists in country music today.